Intervenções fisioterapêuticas em indivíduos com osteoartrite na base do polegar - Tossini, Natália Barbosa (2023)
Introduction: Osteoarthritis is a chronic and degenerative disease that affects synovial joints, especially the thumb carpometacarpal joint. Also known as rhizoarthritis, osteoarthritis of the base of the thumb causes significant functional damage, pain and loss of grip and pinch strength. Its high prevalence, especially in postmenopausal women, added to the clinical picture and public spending, making research in this area important, aiming to improve physiotherapeutic rehabilitation protocols based on scientific evidence. Objectives: This thesis aimed to realize a systematic review with meta-analysis in order to identify and synthesize the effectiveness of conservative physiotherapeutic treatments in individuals with osteoarthritis at the base of the thumb. It was also the objective of this thesis to develop and apply a treatment protocol based on strengthening the 1st dorsal interosseous muscle for these individuals. Methods: A systematic review with meta-analysis was developed, searching the Medline, Embase, CINAHL, PEDro, CENTRAL and Open Gray databases from the beginning until February 2022. Randomized clinical trials were included that used some physical therapy intervention, in individuals with OA at the base of the thumb, compared to a passive or active control group. The quality of the evidence was assessed using the GRADE approach and, the standardized difference of means (SMD) was used to calculate the meta-analysis. The randomized clinical trial included individuals over 40 years of age with a clinical and/or radiographic diagnosis of osteoarthritis at the base of the thumb. Subjects were randomized into an intervention group or a control group. Tools were used to evaluate pain, functionality, grip strength and pinch strength pre and post treatment, which lasted six weeks, with sessions three times a week. Study variables were expressed as mean, standard deviation, the delta of change and percentage. Results: Nineteen studies (n= 1477) were included in the systematic review, and eight (n= 568) underwent meta-analysis. The main result found in the meta-analysis was that the orthosis intervention was superior to the passive control group for pain improvement (SMD= -1.02, p=0.03 and very low evidence), grip strength (SMD= 0.45, p=0.02 and very low evidence) and pinch strength (SMD= 1.78, p=0, 01 and very low evidence), but there was no improvement in physical hand function (p=0.54). In addition, the use of a neoprene orthosis was similar to the use of a thermoplastic orthosis in improving pain (p=0.38), hand physical function (p=0.50), grip strength (p=0 .42) and pinch strength (p=0.14). Finally, the short thermoplastic orthosis was also similar to the use of the long thermoplastic orthosis in improving pain (p=0.88) and physical function of the hand (p=0.58). Regarding the clinical trial, seven individuals were evaluated, four in the intervention group (IG, n=4, 56 years old) and three in the control group (CG, n=3, 63 years old). With the preliminary results of this study, it was possible to observe that both rehabilitation protocols have a positive effect on the improvement of pain level, physical function of the hand, manual dexterity and increasing grip and pinch strength. Conclusion: We conclude that proposing an intervention with an orthosis for individuals with OA at the base of the thumb is better than passive interventions for improving pain, hand physical function, and grip and pinch strength. Regardless of the type of material used to make the orthosis and its design, there is an improvement in the clinical outcomes mentioned above. In addition, we concluded that both the protocol focused on strengthening the 1st dorsal interosseous bone and the conventional protocol brought benefits to individuals with osteoarthritis at the base of the thumb.